2021
DOI: 10.1016/j.jss.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnostic Performance for Thyroid Nodules Classified as Bethesda Category III or IV: How and by Whom Ultrasonography Should be Performed

Abstract: Background: The purpose of this prospective study is to evaluate if the association of Bethesda system and a 3-categories Ultrasonography (US) risk stratification system proposed by the American Association of Clinical Endocrinologists/American College of Endocrinology/Associazione Medici Endocrinologi improves the performance of cytology alone in III or IV categories and if further variables such as US provider (radiologist; endocrinologist, or endocrine surgeon both coming from a dedicated team) influence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, as our review reported, the phenomenon of increased genetic instability and reduction of tumor immunity in multiple cancer patients was confirmed by the case of the woman with medullary, papillary, and RCC (32), a very rare combination, where even if the patient had no previous endocrine history, her mother was affected by breast cancer, another disease deeply connected to TC (4,(45)(46)(47) and the brother presented with RCC, too. A triple malignant tumor was also reported in a male of the same age with thyroid, kidney, and colon being affected (31), demonstrating common expression paths with integrin avß6 in multiple primary cancer (29).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, as our review reported, the phenomenon of increased genetic instability and reduction of tumor immunity in multiple cancer patients was confirmed by the case of the woman with medullary, papillary, and RCC (32), a very rare combination, where even if the patient had no previous endocrine history, her mother was affected by breast cancer, another disease deeply connected to TC (4,(45)(46)(47) and the brother presented with RCC, too. A triple malignant tumor was also reported in a male of the same age with thyroid, kidney, and colon being affected (31), demonstrating common expression paths with integrin avß6 in multiple primary cancer (29).…”
Section: Discussionmentioning
confidence: 70%
“…Thyroid cancer (TC) is one of the most rapidly increasing malignancies in Western countries, with an annual incidence rate of 5.4% in men and 6.5% in women (1). Much of this rise is largely due to early detection using more sensitive diagnostic procedures, including Artificial Intelligence, performed for other medical reasons and able to identify incidental small thyroid nodules, otherwise missed (2)(3)(4). Certain risk factors for TC are female sex, family history of TC, radiation exposure, lymphocytic thyroiditis, and reduced iodine intake (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant nodules tend to cause infiltration and metastasis, thereby permanently compressing the trachea, esophagus, and nerve tissue and compromising patients' daily activities. Therefore, the correct diagnosis and differentiation between benign and malignant thyroid nodules are crucial to patients' treatment and prognosis [8]. Presently, fineneedle aspiration biopsy of thyroid nodules is considered the "gold standard" for differentiating between benign and malignant thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…All these results are consistent with the results of previous studies by Saito et al In addition, in some cases, cystic echo can be detected by ultrasound, which may be due to the rapid growth of metastatic cancer, insufficient blood supply, followed by necrosis and liquefaction, to form cystic degeneration [ 51 ]. Moreover, in a previous study, Gregorio et al further indicated that ultrasounds provided by endocrinologists and surgeons were more accurate in predicting malignancy, compared with those provided by radiologists [ 52 ].…”
Section: Diagnosismentioning
confidence: 99%